Cross-border M&As and innovative activity of acquiring and target firms - Joel Stiebale (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
This paper analyzes the effects of cross-border mergers and acquisitions (M&As) on the innovation of European firms. The results indicate a considerable increase in post-acquisition innovation in the merged entity. This is mainly driven by inventors based in the acquirer's country, while innovation in the target's country tends to decline. The asymmetry of effects between acquiring and target firms increases with pre-acquisition differences in knowledge stocks, indicating a relocation of innovative activities towards more efficient usage within multinational firms. Instrumental variable techniques as well as a propensity-score matching approach indicate that the effect of cross-border M&As on innovation is causal.
Keywords: F23; D22; G34; O31; 330; Multinational Enterprises; Mergers and Acquisitions; Innovation